1999
DOI: 10.1084/jem.189.6.907
|View full text |Cite
|
Sign up to set email alerts
|

An Inflammatory Polypeptide Complex from Staphylococcus epidermidis: Isolation and Characterization

Abstract: Staphylococcus epidermidis releases factors that activate the HIV-1 long terminal repeat, induce cytokine release, and activate nuclear factor κB in cells of macrophage lineage. The active material had a mass of 34,500 daltons, was inactivated by proteases and partitioned into the phenol layer on hot aqueous phenol extraction, and thus was termed phenol-soluble modulin (PSM). High performance liquid chromatography (HPLC) of crude PSM yielded two peaks of activity designated PSM peak 1 and peak 2. MALDI-TOF (ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
162
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(165 citation statements)
references
References 51 publications
2
162
0
1
Order By: Relevance
“…The TLR2 ligand S-(2,3-bispalmitoyloxypropyl)-Cys-Gly-Asp-Pro-Lys-HisPro-Lys-Ser-Phe, Pam(2)CGDPKHPKSF (FSL-1) was purchased from InvivoGen. Phenol-soluble modulin (PSM), derived from Staphylococcus epidermidis, was prepared as described elsewhere (42)(43)(44). FBS and other tissue culture media were obtained from HyClone and BioWhittaker.…”
Section: Bis(palmitoyloxy)-(2-rs)-propyl]-n-palmitoyl-(r)-cys-(s)-sermentioning
confidence: 99%
“…The TLR2 ligand S-(2,3-bispalmitoyloxypropyl)-Cys-Gly-Asp-Pro-Lys-HisPro-Lys-Ser-Phe, Pam(2)CGDPKHPKSF (FSL-1) was purchased from InvivoGen. Phenol-soluble modulin (PSM), derived from Staphylococcus epidermidis, was prepared as described elsewhere (42)(43)(44). FBS and other tissue culture media were obtained from HyClone and BioWhittaker.…”
Section: Bis(palmitoyloxy)-(2-rs)-propyl]-n-palmitoyl-(r)-cys-(s)-sermentioning
confidence: 99%
“…Since THP-1 cells do not express CD14, they were differentiated by 36-h stimulation with vitamin D 3 (0.1 M) before LPS treatment. Phenolsoluble modulin (PSM), a complex of three small secreted polypeptides purified by phenol extraction of supernatants of stationary Staphylococcus epidermidis (26), was obtained from S. Klebanoff (University of Washington). A protein-free, heat-stable, Mycobacterium tuberculosis-conditioned culture supernatant, soluble tuberculosis factor (STF), was obtained from M. J. Fenton (Boston University, Boston, MA).…”
Section: Cells and Reagentsmentioning
confidence: 99%
“…Recently, it has been shown that S. epidermidis produces a pro-inflammatory complex of peptides named phenolsoluble modulin (PSM) based on their partition into the phenol layer on hot phenol extraction (Mehlin et al ., 1999). Phenol-soluble modulin is a stronger inducer of cytokine release from monocytes and THP-1 cells than LTA (Mehlin et al ., 1999), activates the HIV-1 LTR in cells of macrophage lineage, and induces NF-k B production by these cells (Mehlin et al ., 1999). Phenol-soluble modulin also causes degranulation, primes for an enhanced respiratory burst, and inhibits spontaneous apoptosis in human neutrophils (Liles et al ., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of its diverse and strong pro-inflammatory properties, PSM may contribute significantly to sepsis caused by S. epidermidis . Phenol-soluble modulin consists of at least three amphipathic peptides, PSM a , PSM b and PSM g (Mehlin et al ., 1999). PSM g is identical and PSM a similar to S. epidermidis delta toxin.…”
Section: Introductionmentioning
confidence: 99%